Clinical Effect Analysis of Laparoscopic Surgery for Gastric Tumor under Data Mining. (15th September 2021) - Huang, Lingmin; Guo, Jianrong; Yin, Bo; Zeng, Yanqing; Li, Na
Abstract : This paper mainly analyzes the feasibility of laparoscopic local gastrectomy for the treatment of benign gastric tumors, evaluating its curative effect, and the use of traditional Chinese medicine (TCM) such as Hedyotis diffusa, Radix Pseudostellariae, yi, Pinellia ternata, Ophiopogon japonicus, wood fragrance, Perilla, Scutellaria baicalensis, Yuzhu, hawthorn, Artemisia annua, chicken yellow film, nail, and turtle, and clinical symptoms of statistical analysis of data mining. A total of 86 patients with gastric benign tumor were selected as the research object and were divided into observation group and control group with 43 cases in each by the random number table method. The control group received radical gastrectomy for benign tumor under laparoscopy, while the observation group received local gastrectomy under laparoscopy. Perioperative indexes such as operative time, intraoperative blood loss, and length of hospital stay were recorded in the two groups. Serum C-reactive protein (CRP) and carcinoembryonic antigen (CEA) levels were analyzed by enzyme-linked immunosorbent assay (ELISA), and the incidence of complications was compared. Based on the clinical analysis of the drug used, the results of association significance were selected, and the top ten results were selected in order of confidence and grouped according to clinical symptoms, respectively, as follows: (1) abdominal distension: Hedyotis diffusa, Radix Pseudostellariae, Poria cocos, Huckleberry, and Coix seed; (2) dry mouth: Poria cocos, Radix Radix Pseudostellariae, Coix seed, Pinellia tuber, and Radix Ophiopogonis . The results showed that the minimum operation time in the observation group was 159.7 ± 13.07 min and the maximum was 172.57 ± 2.47 min, which was lower than that in the control group (the minimum was 172.46 ± 12.45 min and the maximum was 186.49 ± 24.32 min). The length of hospital stay (6.51 ± 1.29 days) was lower than that in the control group (7.56 ± 1.42 days) (P < 0.05). The CEA and CRP levels decreased significantly in both groups after treatment (P < 0.05 ). However, the observation group's CEA was (4.21 ± 1.05) mg/L and CRP was (8.46 ± 1.25)  μ g/L. In the control group, CEA was (4.18 ± 1.02) mg/L and CRP was (8.39 ± 1.24)  μ g/L. There were no significant differences (P < 0.05 ). The incidence of complications in the observed group was 4.7% lower than 7.0% in the control group (P < 0.05 ). Therefore, laparoscopic local gastric resection for benign gastric tumors can effectively reduce the incidence of CEA and CRP level and complications and improve the perioperative indicators, which is worth popularizing in clinical practice.